Sleep Quality and Its Dimensions in Indonesian Shift and Non-Shift Workers - Shafira, Aviani Rinfi; Anisa, Nur; Assaumi, Nurul Wardah; Adhara, Gaetania Faza; Widayati, Kanthi Arum (HAYATI Journal of Biosciences, 2025)
Sleep quality is crucial in maintaining overall well-being, but is often disrupted by irregular working hours. Shift work, as an example of irregular working hours, has been linked to disrupted sleep due to circadian desynchronization. Previous studies worldwide on the difference in sleep quality between shift and non-shift workers have remained  inconsistent, likely due to variations in work environments, behavioral and sociodemographic factors, and sample sizes. The objective of this study was to evaluate variations in sleep quality between shift and non-shift workers and to explore the underlying factors associated with sleep disruption in both groups. A cross-sectional study was conducted involving 218 workers (99 shift workers and 119 non-shift workers). The Pittsburgh Sleep Quality Index (PSQI) was applied to assess sleep quality, followed by statistical analyses to compare overall and individual component scores between groups. No significant difference was found in global PSQI scores between shift (8.75±3.01) and non-shift workers (8.22±2.8). However, when we evaluated sleep components between the two groups, shift workers showed significantly poorer subjective sleep quality (p = 0.0375) and lower sleep efficiency (p = 0.04471). Further analysis revealed significant associations between PSQI scores, shift frequency, and the number of diseases. Higher shift frequency and a greater number of diseases were associated with increased PSQI scores, indicating poorer sleep quality. These findings suggest that while overall sleep quality may not differ substantially by work schedule, specific components and individual factors, such as health status and workload frequency, contribute to variations in sleep quality.